(untitled) (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
This article continues the series of publications of the author, devoted to the study of communicative-pragmatic problems, the relevance of which there is no doubt in linguistic studies. The researcher paid particular attention to the identification of potential pragmatic verbs in the language of communicative texts bizarre novels of famous Ukrainian writers E. Hutsalo and O. Ilchenko, noting that prahmemy - verb encourage, in particular, updating different expression emotive and evaluative characteristics of the characters of both authors.